UPAYA PENERAPAN AKRUAL DAN PEROLEHAN OPINI WTP DI KOTA PEKALONGAN DARI KACAMATA KURT LEWIN - Riza Muttaqin; Ali Djamhuri; Yeney Widya Prihatiningtias (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2015)
The aim of this research is to reveal and describe the organizational change occured on Pekalongan City Government in implementing public sector accrual accounting and attaining unqualified audit opinion as perceived from the aspects of readiness and strategy implementation by the government based on movement stages following to Lewin’s Organizational Change Theory (1951). The results showed that the change from cash to accrual accounting as well as strategy to achieve unqualified audit opinion is a form of pressure and a process that is deliberately done in order to increase the accountability of the financial statements to be usable for decision-making. The goverment officials have shown resistance and negative impressions to implement of accrual accounting and strategy to achieve unqualified audit opinion. Preparations to implement accrual accounting and strategy to achieve unqualified audit opinion are expected to minimize the attitude of resistance so that the organizational changes can be successful. Preparations to implement of accrual accounting and the strategy to achieve unqualified audit opinion are conducted by issuing Perwal. No. 34 and No. 35 2014, establishing SIMDA and SIMBADA, managing asset, defining a target in its RPJM, following up the BPK’s recommendation, and maintaining common commitment as public sector institution.